SYNPHO (SYNTHETIC PHONICS): A METHOD TO TEACH PRONUNCIATION - Ramli; Winarno; Syuhadah, Nurul Aisyah (LPPM Universitas Muhammadiyah Bulukumba, 2025)
This research aims to determine the effectiveness of synthetic phonics method in learning how to pronounce or pronounce vocabulary in English and students’ perception of using the synthetic phonics method in learning how to pronounce vocabulary in English. This type of research was quasi – experimental with a quantitative approach. In this research, purposive sampling was carried out, and the author used two classes as research sample, namely VII – 8 as the experimental class and VII – 9 as the control class, totaling 30 students each at SMPN 9 Tarakan. Data were analyzed using T – test. The results of the data analysis described that the research result in the experimental class before the students were given treatment illustrated that the average score was 61.03. After receiving treatment, there was a significant increase in the average score of students 84.36; compared to the control class before treatment, the students’ average score was 64.50, and after being given treatment, there was no significant increase in the average score; 65.43. Another component examined in this research was perception, which was very important in synthetic phonics because it influenced how each learner experienced and achieved their goals. Data demonstrated that students’ perceptions of using the Synthetic Phonics method in learning process at SMPN 09 Tarakan were in the ‘positive’ category with a percentage of 85%. The synthetic phonics method provided significant progress toward students’ mastery of word pronunciation. This research has implications for integrating methods in English language learning, and the use of synthetic phonics methods has a positive impact on pronunciation teaching.